The Risk of Bacterial Contamination in Hen Eggs of Sulaimani Poultries - Al-Jaff, Bahrouz M. A. (Sulaimani Journal for Pure and Applied Sciences, 2005)
To evaluate the risk of bacterial contamination and the penetrability of some pathogens through the shell, light brown fertile and brown infertile eggs were subjected to microbiological analyses. The benefit of using 70% ethanol as a proposed disinfectant was assessed also. Non disinfected infertile eggs showed higher contamination with both aerobic and anaerobic bacteria, anaerobic were higher (shells: 8.7.x 102, albumen: 0.28 x 102, yolk: 0.97 x 102 cfu/gm or ml). Disinfecation reduced contamination on shells (for fertile eggs: 85.1% aerobic and 54.4% anaerobic bacteria, for infertile: 65% aerobic and 47.7% anaerobic bacteria). There was no reduction in interior components but the isolation of bacteria from interior components mav belong to a contamination prior to disinfection. Pseudomonas aeruginosa showed higher penetrability when tested artificially in all types of eggs followed by Proteus vulgaris, Staphylococcus cwreus and Escherichia coli respectively regardless whether eggs were disinfected or not. Fertite and intèrtile eggs of Sulaimani poultries were within permissive hygienic quality.